UNIONS in the Precarious Economy. - STONE, KATHERINE V.W. (American Prospect)
The article presents information on the role of labor unions in the benefit enhancement of gig and on-demand workers in the U.S. Topics include the voluntary and flexible nature of work in sectors like retail, restaurant, and janitorial services, understanding the concept of just-in-time scheduling, and the utilization of embedded contract bargaining. It also discusses associational unions, freelance workers, and schedule bidding.